PENGARUH KOMITMEN, STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT MATAHARI DEPARTEMEN STORE - Dian Wahyu Novita; Mira Yona; Moch Aminudin Hadi (EQUILIBIRIA, 2020)
The purpose of this study was to determine the effect of variable work commitment and work stres, work discipline partially and simultaneously on the performance of employees of PT. Matahari Department Store. The population in this study were employees of PT. Matahari Department Store. which numbered 50 people with members of the population sampled as a whole by the questionnaire method.The test results show that work commitment, work stres and work discipline do not all have a positive effect on work effectiveness partially. This test also shows that commitment, work stres and work discipline have a significant and simultaneous effect on work effectiveness. The variables of work commitment, work stres and work discipline are 78.3% and the remaining 21.7%. Explained by other variables not included in this study